Determination of Audit Report Delay in Indonesian Manufacturing Firms Trading on the Stock Market - Syamsuri Rahim; Nur Wahyuni; Yuliantika I. Hady; Asriady Bakri (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
The purpose of this research is to examine how manufacturing firms listed on the Indonesia Stock Exchange determine their audit report lag time. The focus of this study is a manufacturing firm trading on the Indonesia Stock Exchange in 2021. In this study, we rely on information from the Indonesia Stock Exchange's annual reports.Purposive sampling is employed to assemble the data. The study's population consists of all 232 manufacturing firms registered on the Indonesia Stock Exchange; the sample consists of 52 firms that match the study's parameters. SPSS is utilized for the analysis, and the methods employed are descriptive statistics, classical assumptions, and hypotheses. Partial negative and significant effects of firm size, positive and negligible effects of company age, and negative and insignificant effects of audit committee size were found in this study on audit report lag.